2018
DOI: 10.1038/s41598-018-33988-6
|View full text |Cite
|
Sign up to set email alerts
|

Emotion-Specific Affective Theory of Mind Impairment in Parkinson’s Disease

Abstract: The neuropathology of Parkinson’s disease (PD) involves the frontal-subcortical circuit, an area responsible for processing affective theory of mind (ToM). Patients with PD are expected to experience deficits in the affective ToM. This study aims to investigate whether the ability to infer emotion in others is affected in either young-onset Parkinson’s disease (YOPD) or middle-onset PD (MOPD) patients and to test whether the impairments in affective ToM are associated with the motor symptoms. The affective ToM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Moreover, growing evidence has also shown the development of a host of socioaffective troubles in addition to neurocognitive dysfunctions in the disease course of PD [39]. Our previous study also found susceptibility to social cognition in female patients with PD [40]. It is possible that the mechanism underlying the more severe decline of the socioaffective functions is similar to the effect of sex on the neurocognitive dysfunctions observed in this study.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, growing evidence has also shown the development of a host of socioaffective troubles in addition to neurocognitive dysfunctions in the disease course of PD [39]. Our previous study also found susceptibility to social cognition in female patients with PD [40]. It is possible that the mechanism underlying the more severe decline of the socioaffective functions is similar to the effect of sex on the neurocognitive dysfunctions observed in this study.…”
Section: Discussionsupporting
confidence: 81%
“…Sensitivity analyses omitting the study of Yu et al (2018) or Tsuruya et al (2011) or Xi et al (2015) revealed that these studies seemed to have a relatively larger influence on the pooled estimate because, by removing them, the relationship between Affective ToM and educational level became not significant. This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Sociodemographic Correlatesmentioning
confidence: 98%
“…Recently, social cognition impairments have also been reported in PD (Coundouris et al, 2020; Palmeri et al, 2017). Some studies reported a significant association between ToM deficits and PD duration, stage of illness (Kosutzka et al, 2019; Nobis et al, 2017; Romosan et al, 2019; Schmidt et al, 2017; Xi et al, 2015; Yu et al, 2018), or medication (Foley et al, 2019; Kosutzka et al, 2019). Yet, failure to confirm any relationship between ToM dysfunction and clinical variables (including the severity of motor symptoms) in PD has been reported (Bodden et al, 2010b; Enrici et al, 2015, 2017; Giguère-Rancourt et al, 2021; Monetta et al, 2009; Pell et al, 2014; Santangelo et al, 2012; Seubert-Ravelo et al, 2021; Tsuruya et al, 2011), probably explained by different weights of some cognitive domains or neuropsychiatric states.…”
mentioning
confidence: 99%
“…Moreover, emotion recognition is essential for detecting brain alterations or early signs of psychological/neurological disorders. Evidence has shown that patients with neurodegenerative diseases (e.g., Alzheimer’s disease [ 8 ] and Parkinson’s disease [ 9 ]) or psychiatric disorders (e.g., autism spectrum disorder and schizophrenia [ 10 ]) are found to have impairments in facial emotion recognition ability. Furthermore, it has also been shown that alexithymia is a transdiagnostic construct [ 11 ], and detecting difficulties in emotion recognition could facilitate the diagnosis of psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%